NIX quality control colorimeter can evaluate color of yerba mate - Câmara, Otávio Pereira; Costa, Emanuele; Prado, Naimara Vieira do; Lucchetta, Luciano; Moresco, Karla Suzana; Burgardt, Vânia Cássia Fonseca; Machado-Lunkes, Alessandra (Food Science and Technology, 2025)
Color is a crucial attribute in the herbal market. One of the primary parameters consumers deem essential when selecting a product is the green color intensity, which is directly associated with the freshness of Ilex paraguariensis yerba mate. During the yerba mate production process, there is a need for instrumental tools to evaluate color, which aim to minimize the empirical method of assessment in the production process. This study aimed to compare the color of yerba mate samples using the Nix Quality Control and the Konica Minolta CR-410 colorimeter and to evaluate the Nix Quality Control’s potential for scientific research and application within the yerba mate production sector. The CIELAB color space of 219 yerba mate batches from various storage periods was analyzed using Konica Minolta and Nix Quality Control colorimeters. The highest correlation observed between the equipment was for the parameter a∗, with r = .931 Control charts, which indicated a good agreement between Nix Quality Control and Minolta for a∗ and b∗ parameters. Since a∗ and b∗ are the most significant color parameters for yerba mate, it is possible to say that the Nix Quality Control colorimeter can serve as a suitable substitute for the Minolta.